Clipping Pada Aneurisma Intrakranial - I Made Arya Yogiswara Mahayasa; Ilsa Hunaifi; Stephanie Elizabeth Gunawan; Setyawati Asih Putri (Jurnal Biologi Tropis, 2023)
An aneurysm is an abnormal formation of a blood vessel. Aneurysms are divided into 4 according to their shape (saccular, microaneurysm, giant, and fusiform). The formation of an aneurysm is caused by many factors (patient risk factors, hemodynamic stress, and involvement of cytokines and inflammatory mediators as well as macrophages, T cells, and mast cells). The diagnosis of an aneurysm is carried out with the help of tools such as MRA and CT angiography. In providing management of an unruptured aneurysm, consideration is needed by taking into account many factors, to facilitate this consideration, an assessment can be carried out first, it can be carried out using a scoring system called Unruptured Intracranial Aneurysm Treatment Score (UIATS). One of the time-proven aneurysm management is to perform aneurysm clipping. Clipping has advantages such as having a low recurrence rate and has disadvantages such as being invasive with the need to perform craniotomy. Complications that can arise from doing clipping in aneurysms such as infection, allergic reactions to anesthetic drugs, stroke, seizures, cerebral edema. Prognosis of management using the clipping method is good.